Human nature or humanity: between genes and values - Tuchańska, Barbara (Hybris, 2012)
We are within nature and culture, conditioned simultaneously by genes and meanings. This form of our self-understanding is the result of fundamental modifications that happened in modern philosophical anthropology and of the impact of the natural Science. In modern philosophy three types of approaches to the human situation were constituted at different times: the idealist, the naturalist, and the culturalist, and the problem of whether humanity is natural (biological) or cultural has begun to take precedence over the issue of human supernatural roots. Both approaches are presented, their presuppositions discussed, and arguments in favor of a version of the culturalist approach. Only the culturalist approach allows us to understand our own self-constitution and, in particular, our self-reflectivity, as well as the naturalist attempts to ignore them and immerse ourselves in nature